2004
DOI: 10.1002/jmv.20013
|View full text |Cite
|
Sign up to set email alerts
|

Latent human papillomavirus infection is comparable in the larynx and trachea

Abstract: Recurrent respiratory papillomas are benign airway tumors caused by Human Papillomaviruses (HPVs) types 6 and 11. The disease is characterized by multiple recurrences of papillomas following surgical removal, caused by activation of latent HPV DNA. Most patients have laryngeal disease, while only a small subset has tracheal involvement. We have asked whether the lower frequency of tracheal papillomas was due to reduced prevalence of latent/subclinical tracheal HPV infection or reduced likelihood of activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 34 publications
4
44
0
1
Order By: Relevance
“…It has been reported that low-risk (i.e., low malignant potential) HPV types 6 and 11 cause about 90% of cases of recurrent respiratory papillomatosis [1,4]. Their existence as latent infections in morphologically normal tissue of the airway and are believed to be the source of recurrent disease [10,11]. The association between the virus and the characteristic lesions of this disease was proven with electron microscopic studies and DNA analysis.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that low-risk (i.e., low malignant potential) HPV types 6 and 11 cause about 90% of cases of recurrent respiratory papillomatosis [1,4]. Their existence as latent infections in morphologically normal tissue of the airway and are believed to be the source of recurrent disease [10,11]. The association between the virus and the characteristic lesions of this disease was proven with electron microscopic studies and DNA analysis.…”
Section: Discussionmentioning
confidence: 97%
“…This report proposed that the low frequency of tracheal disease reflects a lower frequency of activation. 5) Risk factors leading to virus activation in RRP have not been recognized; however, gastroesophageal reflux disease has been suggested as a possible factor. 10) Malignant degeneration into squamous cell carcinoma occurs in 3% to 5% of papilloma patients and more often in patients with a history of smoking or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothesizing that HPV infection activates the EGFR→Rac1→p38→COX-2 pathway, we compared primary biopsies from laryngeal papillomas, which have active HPV infection, to clinically normal biopsies from the same patient, which have either latent or no HPV infection (15). Western blot analysis of the EGFR confirmed increased expression is limited to papillomas of RRP patients ( Figure 1A).…”
Section: Host Signaling In Rrp Patientsmentioning
confidence: 98%